Reliability of the Home Hearing Test: Implications for Public Health - Mosley, Cornetta L. (J Am Acad Audiol, 2018)
BACKGROUND: The projected increase in the aging population raises concerns about how to manage the healthcare needs in a cost effective way. Within hearing healthcare, there are currently too few audiologists to meet the expected demand, and training more professionals may not be a feasible way of addressing this problem. For this reason, there is a need to develop different ways of assessing hearing sensitivity that can be conducted accurately and inexpensively when a certified audiologist and/or sound-attenuated booth is unavailable. More specifically, there is a need to determine if the HHT can yield accurate and reliable data from older adults with varying degrees of hearing loss. PURPOSE: To compare audiometric thresholds obtained using the Etymotic ‘Home Hearing Test’ (HHT), an automated pure-tone air-conduction test, to those obtained using manual audiometry, among older adults with varying degrees of hearing loss. STUDY SAMPLE: Participants were 112 English-speaking adults (58% Female), aged 60 years and older. Participants were excluded from this study if otoscopy revealed cerumen impaction and/or suspected ear pathology. INTERVENTION: All participants completed the HHT on tablet computers in a carpeted classroom and MA in a double-walled sound attenuated booth using insert earphones for both measures. Both measures were completed in the same test session and the order of testing (MA vs. HHT) was counterbalanced. DATA COLLECTION AND ANALYSIS: Absolute differences in thresholds measurements (in dBHL) were calculated across all ears (n = 224 ears) and for all frequencies (octave frequencies from 0.5 – 8 kHz). Correlation and multiple linear regression analyses were conducted to determine if thresholds obtained using the HHT significantly correlated with thresholds using MA. Mean thresholds for each method (HHT and MA) were compared using correlation analyses for each test frequency. Multiple linear regression analysis was used to examine the relationship between the four-frequency PTA (average threshold at 0.5, 1, 2, and 4 kHz) in the better-hearing ear measured using the HHT and a set of seven independent factors: four-frequency PTA in the better-hearing ear measured via MA, treatment group (HHT vs. MA), age, gender, and degree of hearing loss (mild, moderate, > moderate). RESULTS: Correlation analyses revealed frequency-specific correlations, ranging from 0.91 – 0.97, for air-conduction thresholds obtained using the HHT and MA. Mean HHT thresholds were significantly correlated with mean MA thresholds in both ears across the frequency range. This relationship held true across different degrees of hearing loss. The regression model accounted for a significant amount of variance in the HHT better ear PTA, with MA better-ear PTA being the only significant predictor in our final model, with no effect of degree of loss, age or gender. CONCLUSIONS: The HHT is an accurate and cost effective method of establishing pure-tone air conduction thresholds, when compared to manual audiometry. Therefore, the HHT can be used as a tool to acquire accurate hearing thresholds from older adults, in-group settings, without the use of a sound-attenuated booth or a certified audiologist.